Cyanobacteria Scytonema javanicum and Scytonema ocellatum Lipopolysaccharides Elicit Release of Superoxide Anion, Matrix-Metalloproteinase-9, Cytokines and Chemokines by Rat Microglia In Vitro - Lucas C. Klemm; Evan Czerwonka; Mary L. Hall; Philip G. Williams; Alejandro M. S. Mayer (Toxins, 2018)
Cosmopolitan Gram-negative cyanobacteria may affect human and animal health by contaminating terrestrial, marine and freshwater environments with toxins, such as lipopolysaccharide (LPS). The cyanobacterial genus Scytonema (S) produces several toxins, but to our knowledge the bioactivity of genus Scytonema LPS has not been investigated. We recently reported that cyanobacterium Oscillatoria sp. LPS elicited classical and alternative activation of rat microglia in vitro. Thus, we hypothesized that treatment of brain microglia in vitro with either cyanobacteria S. javanicum or S. ocellatum LPS might stimulate classical and alternative activation with concomitant release of superoxide anion (O2−), matrix metalloproteinase-9 (MMP-9), cytokines and chemokines. Microglia were isolated from neonatal rats and treated in vitro with either S. javanicum LPS, S. ocellatum LPS, or E. coli LPS (positive control), in a concentration-dependent manner, for 18 h at 35.9 °C. We observed that treatment of microglia with either E. coli LPS, S. javanicum or S. ocellatum LPS generated statistically significant and concentration-dependent O2−, MMP-9 and pro-inflammatory cytokines IL-6 and TNF-α, pro-inflammatory chemokines MIP-2/CXCL-2, CINC-1/CXCL-1 and MIP-1α/CCL3, and the anti-inflammatory cytokine IL-10. Thus, our results provide experimental support for our working hypothesis because both S. javanicum and S. ocellatum LPS elicited classical and alternative activation of microglia and concomitant release of O2−, MMP-9, cytokines and chemokines in a concentration-dependent manner in vitro. To our knowledge this is the first report on the toxicity of cyanobacteria S. javanicum and S. ocellatum LPS to microglia, an immune cell type involved in neuroinflammation and neurotoxicity in the central nervous system.